Analyzing Trends in Quality and Character Education: A Bibliometric Approach - Alfian; Komariah, Aan; Kurniady, Dedy Achmad; Herawan, Endang (Indonesian Research Journal in Education |IRJE|, 2024)
This research employs a bibliometric approach to analyze research trends in quality and character education, utilizing data from 161 articles sourced from the SCOPUS database. The analysis reveals central themes, such as character education, ethical development, and curriculum integration, highlighting significant contributions from prominent authors and global collaborations. Despite extensive research, gaps were identified in practical implementation strategies and the exploration of character education's role in addressing societal issues like corruption. The findings underscore the need for future research to develop effective, culturally responsive strategies and to explore digital and interdisciplinary approaches. By addressing these gaps, this study aims to enhance the understanding and integration of quality and character education, contributing to improved educational outcomes and holistic student development.